The Outlook for international bank lending : a survey of opinion among leading international bankers - Mendelsohn, Stefan; Group of Thirty (New York, N.Y. : The Group, 1981)
This book is a handy work of the group of thirty with aim examine problems associated with balance of payments in developing countries. It further resolved to examine critical questionnaire questions posed to the group to 20 top banks across the world.
asm; 05/03/19
Loans
Keywords: Loans, Foreign